2008
DOI: 10.1007/s00710-008-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Late Miocene to Pleistocene potassic volcanism in the Republic of Macedonia

Abstract: The potassic (K) to ultrapotassic (UK) volcanic rocks cropping out in the Vardar Zone of Macedonia and southern Serbia span in age from Late Miocene (6.57 Ма)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…SiO2 vs. Na2O + K2O and SiO2 vs. 87Sr/86Sr diagrams for Sava zone and Vardar zone including sign legend. Data from Balen and Pamić, 2001;Cvetković et al, 2004;Pamić et al, 1995;Pamić and Balen, 2001;Prelević et al, 2005Prelević et al, , 2007Yanev et al, 2008. Symbols are shown.…”
Section: Resultsmentioning
confidence: 99%
“…SiO2 vs. Na2O + K2O and SiO2 vs. 87Sr/86Sr diagrams for Sava zone and Vardar zone including sign legend. Data from Balen and Pamić, 2001;Cvetković et al, 2004;Pamić et al, 1995;Pamić and Balen, 2001;Prelević et al, 2005Prelević et al, , 2007Yanev et al, 2008. Symbols are shown.…”
Section: Resultsmentioning
confidence: 99%
“…A hyperbolic mixing curve for different ratios of (Sr/Nd) EMII /(Sr/Nd) DM shows mixing between a depleted mantle (DM) and an enriched mantle (EMII) source. It illustrates that the measured Sr-Nd isotopic ratio is a result of magma mixing or crustal contamination (Cvetković et al, 2004;Depaolo and Wasserburg, 1979;Graf, 2001;Marchev et al, 2004;Prelević et al, 2005;Rollinson, 1993;Yanev et al, 2008 Nd vs. time plot (age in Ma). It shows the evolution of Nd isotope ratios during the last 35 Ma in Macedonia and Serbia (Cvetković et al, 2004;Graf, 2001;Marchev et al, 2004;Prelević et al, 2005;Yanev et al, 2008).…”
Section: Ree/hf In Zirconmentioning
confidence: 94%
“…Only a few isotopic analyses are available for young magmatic rocks of this region (intrusive rocks from F.Y.R. of Macedonia, Serbia and Bulgaria; Yanev et al, 2008;Prelević et al, 2005;Marchev et al, 2004;Cvetković et al, 2004) which are plotted with our data on Fig. 7A and B (Table 4).…”
Section: Sr and Nd Isotopesmentioning
confidence: 99%
“…in FYR Macedonia to Voras Mts. in Greece (Janković, 1993;Pe-Piper and Piper 2002;Yanev et al 2008). The major elemental components of the Allchar deposit are Sb, As, Tl, Fe and Au, accompanied by minor Hg and Ba, and traces of Pb, Zn, Cu.…”
Section: Main Geological Characteristics Of the Allchar Depositmentioning
confidence: 99%
“…The following were analyzed: sanidines from andesite from the Crven Dol locality (Troesh and Franc, 1992), biotites, feldspars and amphiboles from latite from the Kojčov Rid locality (Neubauer et al 2009a), feldspars from the zones of intensively altered volcanites from the ADR and Rudina localities (Neubauer et al, 2009a), biotites from tuffs (Neubauer et al, 2009a)from the Vitačevo locality, and feldspars from tuffs from the Rudina locality (Neubauer et al, 2009a). The data on the petrologic and geochemical characteristics of the analyzed rocks may be found in the papers of Boev (1988), Yanev et al (2008) and Neubauer et al (2009a and2009b), whereas the results of the conducted investigations are shown in Table 1. Based on the above, it is possible to infer that two basic stages of volcanogenic-intrusive activity occurred in the broader Allchar deposit area: 1-the older, Miocene stage of volcanic activity, comprising the dikes of calc-alkali rocks fully hydrothermally altered during Pliocene and 2-a younger stage of volcanism of Pliocene age, which developed in the broader Allchar deposit area.…”
Section: The Age Of Mineralization and Of Volcanic Rocksmentioning
confidence: 99%